2012
DOI: 10.4236/jwarp.2012.45030
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Neuro-Fuzzy Logic System for Heavy Metal Sorption in Aquatic Environments

Abstract: In this paper, adaptive neuro-fuzzy inference system ANFIS is used to assess conditions required for aquatic systems to serve as a sink for metal removal; it is used to generate information on the behavior of heavy metals (mercury) in water in relation to its uptake by bio-species (e.g. bacteria, fungi, algae, etc.) and adsorption to sediments. The approach of this research entails training fuzzy inference system by neural networks. The process is useful when there is interrelation between variables and no eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Also, Rebouh et al [35] applied the ANFIS technique for the prediction of metal ions removal capacity from aqueous solution by wheat straw biosorbent. Moreover, Qasaimeh et al exploited the ANFIS to assess the conditions required for aquatic systems to serve as a sink for metal ions removal [36]. The adsorption modeling basically has two advantages: (1) development a relation between input and output effective parameters irrespective of behavior and (2) finding the optimal condition for the removal of target pollutant which has been verified by confirmatory experimental run.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Rebouh et al [35] applied the ANFIS technique for the prediction of metal ions removal capacity from aqueous solution by wheat straw biosorbent. Moreover, Qasaimeh et al exploited the ANFIS to assess the conditions required for aquatic systems to serve as a sink for metal ions removal [36]. The adsorption modeling basically has two advantages: (1) development a relation between input and output effective parameters irrespective of behavior and (2) finding the optimal condition for the removal of target pollutant which has been verified by confirmatory experimental run.…”
Section: Introductionmentioning
confidence: 99%
“…Yılmaz Öztürk et al (2014) applied fuzzy logic assessment method for heavy metal pollution in Apa Dam Lake and indicated that fuzzy logic methods suggested more precise evaluation than traditional classification methods. Qasaimeh et al (2012) used ANFIS for heavy metal sorption in aquatic environments and found a higher correlation of 0.98 between observed data and modelled results. Yesilnacar and Sahinkaya (2012) used ANN for prediction of sulfate and sodium adsorption ratio in an unconfined aquifer in Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, releasing of Cd into the aquatic environment from industrial activities is a serious threat for the aquatic ecosystems (Qasaimeh, Abdallah, & Bani Hani, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic algorithms (GA) can be applied to natural and real world problems. For instance, a fuzzy logic system used the genetic algorithms and neural networks to create fuzzy knowledge bases and rules to evaluate the capability of wetlands to remove mercury [17] [18].…”
Section: Natural Selectionmentioning
confidence: 99%